Impact of COVID-19 on paediatric emergency department attendances at four English hospitals. Issue 1 (8th February 2022) - Aldridge, Patrick; Wilson, Sarah; Roland, Damian; McCann, Gerard; Burridge, Richard George
Abstract : Paediatric emergency department (PED) attendances reduced worldwide during the COVID-19 pandemic (2020) but anecdotally babies under 30 days (BUD) appeared less affected. We collated monthly PED attendances (16 years and under) across four hospitals (three district general hospitals and a tertiary specialist PED) in England, UK from January 2017 to December 2020. Gross PED attendances dropped by 34% in 2020 (n=98 256) compared to 2019 (n=148 640). However, cumulative BUD attendances dropped by only 6% in 2020 (n=3922) compared to 2019 (n=4162). Monthly site-specific attendances showed marginal variation. PED attendances broadly decreased in 2020 with less of an impact on BUD.